Amgad Center sebagai Repositori Digital untuk Penelusuran Sumber Informasi Keislaman - Lailatur Rahmi; Ikhlimah Qibtiyah Hsb; Salsabila Salsabila; Ilya Husna (Maktabatuna, 2025)
The rapid growth of digital scholarship has transformed access to Islamic manuscripts from scarce physical holdings into open, networked information resources. This article examines the Amgad Center as a digital information service supporting manuscript-based research. Using web content analysis of the official site (amgad.center ), we review core features—manuscript catalogues, scholarly consultation, thesis/dissertation database, heritage library, and training/activities—and evaluate them through Belkin’s Information Needs (ASK) and Chowdhury’s digital information services framework. The analysis shows that Amgad Center functions not only as a gateway to distributed digitized manuscripts but also as a scholarly enablement platform: faceted discovery aligned with manuscript structures (e.g., author, scribe, library, prolog/epilog), curated secondary resources, and structured training/forums that build manuscript literacy and research capacity. These services are particularly relevant for academic communities in Islamic higher education (e.g., Indonesian PTKIN), where reliable access to primary sources and guided research support remain uneven. The study contributes an evaluative mapping of Amgad Center’s features to user information needs and service quality dimensions, highlighting opportunities for multilingual access and user-oriented enhancements to strengthen digital ecosystems for Islamic intellectual heritage.